"Legitimacy Worlds": Prosaic Writers’ Strategies of Legitimation in Russian Literary Field - Golovneva, Anastasiya (Journal of Economic Sociology, 2015)
This article is the result of empirical research of prose writers’ strategies of legitimation in St. Petersburg. The concept of legitimacy in the field of cultural production is a problematic area in sociological research. The paper deals with the transformation of attempts to conceptualize legitimacy in the cultural industries, from the thesis of the “high” culture privileged legitimacy to the recognition of multiple principles of separation, legitimate and illegitimate in this area. In this study, the legitimacy of the field of literature actors is limited to the market of literary publications. Publishing houses, literary awards, as well as the associated “thick” literary journals, critics, and journalists are considered to be the institutional sources of legitimacy in this area. The aim of the work is to analyze the strategies implemented by novelists in Russia’s literary field to achieve legitimacy in the field in a situation of uncertainty of principles of selection agents and the risk of not attaining a legitimate position within it. The empirical basis of the study consists of the narratives of writers and other agents in the literary field, collected using the methods of semi-structured interviews and participant observation at the public presentations of writers’ books. As a result, the author accounts for legitimation of writers as work in three directions: of reaching literary legitimacy, based on the fact of text creation, institutional legitimacy of two forms, published form (a writer becomes a part an institution in order to have their book published) and expert form (a writer assumes the position of an expert in a given field); and the public recognition variety of legitimacy, based on the public interest in the author. Each of these types of legitimacy implies a certain set of strategies to achieve it, employed by prose writers.